Anti-deformation environment-friendly composite board and production process thereof
By modifying bamboo fibers with aminosilicone and pyroglutamic acid-polyethylene glycol ester, the bonding strength and compatibility with polylactic acid are improved, resulting in a composite board with enhanced mechanical properties and stability.
Patent Information
- Application Number
- CN202411336843.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Wood-plastic composite boards suffer from poor stability and impact resistance due to inadequate bonding between plant fibers and plastics.
A method involving the modification of bamboo fibers with aminosilicone and pyroglutamic acid-polyethylene glycol ester, combined with polylactic acid, through specific reaction steps to enhance bonding strength and compatibility, resulting in a composite board with improved mechanical properties.
The modified composite board exhibits enhanced strength, toughness, and impact resistance, addressing the stability issues of traditional wood-plastic composite boards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite boards, in particular to an anti-deformation environmentally friendly composite board and a production process thereof. Background Art
[0002] Wood-plastic composite board is a new type of material produced by using polymers instead of adhesives, mixing with plant fibers and then extruding, injection molding and other plastic processing processes. It is widely used in building materials construction, home decoration, logistics packaging and other industries. Because the raw materials of wood-plastic composite boards are polymers and plant fibers, they can replace solid wood in many fields and save resources. They are in line with the concept of environmental protection and are favored by people. Compared with solid wood boards, wood-plastic composite boards have the characteristics of wide sources of raw materials, good processability, good corrosion resistance, good coloring performance, good reusability, and green and environmentally friendly products. However, due to the poor bonding between plant fibers and plastics, wood-plastic composite boards have problems with poor stability and impact resistance. Summary of the invention
[0003] The purpose of the present invention is to provide an anti-deformation environmentally friendly composite board and a production process thereof, so as to solve the problems of poor stability and impact resistance of wood-plastic composite boards.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing an anti-deformation environmentally friendly composite board, the preparation method comprising: The aminosilicone modified bamboo fiber, pyroglutamic acid-polyethylene glycol ester and polylactic acid are mixed evenly, kneaded at 180-200°C for 25-35 minutes, cooled after kneading, and crushed to obtain composite board particles, and the composite board particles are hot-pressed at a pressure of 4-6 MPa, a temperature of 170-190°C, and a time of 50-70 minutes. After the hot pressing is completed, the composite board particles are cooled to 110-130°C, pressed again for shaping, the secondary shaping pressure is 4-6 MPa, and the secondary shaping time is 10-20 minutes. After shaping, the composite board is naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant environmentally friendly composite board.
[0005] As a limitation of the present invention, the mass ratio of aminosilicone modified bamboo fiber, pyroglutamic acid-polyethylene glycol ester, and polylactic acid is (18-22):(24-26):(53-57).
[0006] As a limitation of the present invention, the preparation method of the modified bamboo fiber is: The bamboo fiber is washed with deionized water to remove dust and impurities, and then dried at 55-65° C. to obtain dried bamboo fiber; 2,2,6,6-tetramethylpiperidinium oxide, sodium bromide, sodium hypochlorite and deionized water are mixed and stirred evenly to obtain tetramethylpiperidinium oxide solution; the dried bamboo fiber and the tetramethylpiperidinium oxide solution are mixed, the pH is adjusted to be alkaline, and the mixture is reacted at 55-65° C. and 200-400 rpm for 0.5-1.5 h; after the reaction is completed, the bamboo fiber is filtered out, washed with deionized water, and dried at 25-30° C. for 22-26 h to obtain carboxylated bamboo fiber; Tetramethylammonium hydroxide, triethylamine, ethanol, acetonitrile and deionized water are mixed to obtain a mixed amine solution, KH-550 is slowly added dropwise to the mixed amine solution, refluxed at 65-75°C and 200-400rpm for 16-20h, and after refluxed, vacuum heated, the solvent is removed, and washed with toluene to obtain amino silsesquioxane; The aminosilsesquioxane and deionized water are mixed, and ultrasonically dispersed for 3 to 5 hours to obtain an aminosilsesquioxane dispersion. The aminosilsesquioxane dispersion and carboxylated bamboo fiber are mixed, and reacted at 35 to 45° C. for 10 to 14 hours. After the reaction is completed, the mixture is filtered and dried at 55 to 65° C. to obtain aminosiloxane-modified bamboo fiber.
[0007] As a limitation of the present invention, the tetramethylpiperidinium oxide solution includes, by mass, 1.56 to 1.58 parts of 2,2,6,6-tetramethylpiperidinium oxide, 10.0 to 10.4 parts of sodium bromide, 44.2 to 44.6 parts of sodium hypochlorite, and 43.5 to 44.5 parts of deionized water.
[0008] As a limitation of the present invention, the mixed amine solution includes, by mass, 0.2 to 0.4 parts of tetramethylammonium hydroxide, 0.2 to 0.4 parts of triethylamine, 18 to 22 parts of ethanol, 8 to 12 parts of acetonitrile, and 28 to 32 parts of deionized water.
[0009] As a limitation of the present invention, the aminosiloxane-modified bamboo fiber includes, by weight, 0.3 to 0.5 parts of aminosilsesquioxane, 3 to 5 parts of carboxylated bamboo fiber, and 90 to 100 parts of deionized water.
[0010] As a limitation of the present invention, the preparation method of the pyroglutamic acid-polyethylene glycol ester is: Mix pyroglutamic acid, polyethylene glycol and scandium trifluoromethanesulfonate, react at 170-190°C for 2-4h in nitrogen as protective gas, heat to 195-205°C, continue to react for 1-3h, cool to 125-135°C after the reaction is completed, vacuum filter and dry to obtain pyroglutamic acid-polyethylene glycol ester.
[0011] As a limitation of the present invention, the pyroglutamic acid-polyethylene glycol ester includes 12.3 to 12.7 parts of pyroglutamic acid, 48.1 to 48.5 parts of polyethylene glycol, and 0.03 to 0.05 parts of scandium trifluoromethanesulfonate, by weight.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The bamboo fiber is oxidized with a 2,2,6,6-tetramethylpiperidinium oxide / sodium bromide / sodium hypochlorite system, and the hydroxyl groups on the surface of the bamboo fiber are oxidized into carboxyl groups, so that the amino silsesquioxane is grafted onto the bamboo fiber, thereby increasing the contact area of the fiber surface, increasing the roughness of the fiber surface, promoting the formation of hydrogen bonds between the fiber and the polymer, enhancing the bonding strength between the fiber and the polymer, improving the compatibility between the bamboo fiber and the polymer, and improving the mechanical properties of the bamboo fiber, thereby improving the strength, toughness, impact resistance and other properties of the composite material.
[0013] The use of pyroglutamic acid to modify polyethylene glycol improves the structure of polyethylene glycol, increases the molecular weight of polyethylene glycol, forms intermolecular hydrogen bonds with polyethylene glycol, and then forms a two-dimensional hydrogen bond network, which reduces the migration rate of polyethylene glycol in polylactic acid and the tendency of phase separation, increases the compatibility between polyethylene glycol and polylactic acid, reduces the interaction force between polylactic acid molecular chains, and increases the activity of polylactic acid molecular chain segments, thereby improving the toughness and elongation at break of the composite material and other properties. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Bamboo fiber (120 mesh) was provided by Anhui Sentai, polyethylene glycol (Mn=2000) was provided by Jiangsu Runfeng, pyroglutamic acid (H815789), 2,2,6,6-tetramethylpiperidinoxide (T819129), and KH-550 (A800523) were provided by Shanghai McLean.
[0016] Embodiment 1: A method for preparing an anti-deformation environmentally friendly composite board, specifically: Step 1: Preparation of carboxylated bamboo fiber The bamboo fiber was washed with deionized water to remove dust and impurities, and then dried at 60°C to obtain dry bamboo fiber. 1.57 parts of 2,2,6,6-tetramethylpiperidine oxide, 10.2 parts of sodium bromide, 44.4 parts of sodium hypochlorite and 43.9 parts of deionized water were mixed and stirred to obtain tetramethylpiperidine oxide solution. 5 parts of dry bamboo fiber and 100 parts of tetramethylpiperidine oxide solution were mixed, and the pH was adjusted to 10.0 with sodium hydroxide solution. The reaction was carried out at 60°C and 300rpm for 1.0h. After the reaction was completed, the bamboo fiber was filtered out, washed with deionized water, and dried at 27°C for 24h to obtain carboxylated bamboo fiber.
[0017] Step 2: Preparation of Aminated Silsesquioxane By mass, 0.3 parts of tetramethylammonium hydroxide, 0.3 parts of triethylamine, 20 parts of ethanol, 10 parts of acetonitrile and 30 parts of deionized water were mixed to obtain a mixed amine solution. 20 parts of KH-550 were slowly added dropwise to 60.6 parts of the mixed amine solution, and refluxed at 70°C and 300rpm for 18h. After reflux, vacuum heating was performed to remove the solvent and the solution was washed with toluene to obtain amino silsesquioxane.
[0018] Step 3: Preparation of aminosiloxane-modified bamboo fiber By mass, 0.4 parts of amino silsesquioxane and 95.6 parts of deionized water were mixed and ultrasonically dispersed for 4 hours to obtain an amino silsesquioxane dispersion. 96 parts of the amino silsesquioxane dispersion and 4 parts of carboxylated bamboo fiber were mixed and reacted at 40°C for 12 hours. After the reaction was completed, it was filtered and dried at 60°C to obtain amino siloxane-modified bamboo fiber.
[0019] Step 4: Preparation of pyroglutamic acid-polyethylene glycol ester By mass, 12.5 parts of pyroglutamic acid, 48.3 parts of polyethylene glycol, and 0.04 parts of scandium trifluoromethanesulfonate were mixed, reacted at 180°C for 3 hours in nitrogen as a protective gas, heated to 200°C, and continued to react for 2 hours. After the reaction was completed, the temperature was lowered to 130°C, vacuum filtered, and dried to obtain pyroglutamic acid-polyethylene glycol ester.
[0020] Step 5: Prepare deformation-resistant environmentally friendly composite board By mass, 20 parts of aminosilicone modified bamboo fiber, 25 parts of pyroglutamic acid-polyethylene glycol ester and 55 parts of polylactic acid were mixed evenly, kneaded at 190°C for 30 minutes, cooled after kneading, and crushed to obtain composite board particles. The composite board particles were hot-pressed and compounded at a hot-pressing pressure of 5MPa, a hot-pressing temperature of 180°C, and a hot-pressing time of 60min. After the hot-pressing was completed, the particles were cooled to 120°C and pressed again for shaping. The secondary shaping pressure was 5MPa and the secondary shaping time was 15min. After shaping, the particles were naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant and environmentally friendly composite board.
[0021] Embodiment 2: A method for preparing a deformation-resistant environmentally friendly composite board, specifically: Step 1: Preparation of carboxylated bamboo fiber The bamboo fiber was washed with deionized water to remove dust and impurities, and then dried at 60°C to obtain dry bamboo fiber. 1.57 parts of 2,2,6,6-tetramethylpiperidine oxide, 10.2 parts of sodium bromide, 44.4 parts of sodium hypochlorite and 43.9 parts of deionized water were mixed and stirred to obtain tetramethylpiperidine oxide solution. 5 parts of dry bamboo fiber and 100 parts of tetramethylpiperidine oxide solution were mixed, and the pH was adjusted to 10.0 with sodium hydroxide solution. The reaction was carried out at 60°C and 300rpm for 1.0h. After the reaction was completed, the bamboo fiber was filtered out, washed with deionized water, and dried at 27°C for 24h to obtain carboxylated bamboo fiber.
[0022] Step 2: Preparation of Aminated Silsesquioxane By mass, 0.3 parts of tetramethylammonium hydroxide, 0.3 parts of triethylamine, 20 parts of ethanol, 10 parts of acetonitrile and 30 parts of deionized water were mixed to obtain a mixed amine solution. 20 parts of KH-550 were slowly added dropwise to 60.6 parts of the mixed amine solution, and refluxed at 70°C and 300rpm for 18h. After reflux, vacuum heating was performed to remove the solvent and the solution was washed with toluene to obtain amino silsesquioxane.
[0023] Step 3: Preparation of aminosiloxane-modified bamboo fiber By mass, 0.4 parts of amino silsesquioxane and 95.6 parts of deionized water were mixed and ultrasonically dispersed for 4 hours to obtain an amino silsesquioxane dispersion. 96 parts of the amino silsesquioxane dispersion and 4 parts of carboxylated bamboo fiber were mixed and reacted at 40°C for 12 hours. After the reaction was completed, it was filtered and dried at 60°C to obtain amino siloxane-modified bamboo fiber.
[0024] Step 4: Preparation of pyroglutamic acid-polyethylene glycol ester By mass, 12.5 parts of pyroglutamic acid, 48.3 parts of polyethylene glycol, and 0.04 parts of scandium trifluoromethanesulfonate were mixed, reacted at 180°C for 3 hours in nitrogen as a protective gas, heated to 200°C, and continued to react for 2 hours. After the reaction was completed, the temperature was lowered to 130°C, vacuum filtered, and dried to obtain pyroglutamic acid-polyethylene glycol ester.
[0025] Step 5: Prepare deformation-resistant environmentally friendly composite board By mass, 18 parts of aminosilicone modified bamboo fiber, 24 parts of pyroglutamic acid-polyethylene glycol ester and 53 parts of polylactic acid were mixed evenly, kneaded at 190°C for 30 minutes, cooled after kneading, and crushed to obtain composite board particles. The composite board particles were hot-pressed and compounded at a hot pressing pressure of 5MPa, a hot pressing temperature of 180°C, and a hot pressing time of 60min. After the hot pressing, they were cooled to 120°C and pressed again for shaping. The secondary shaping pressure was 5MPa and the secondary shaping time was 15min. After shaping, they were naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant and environmentally friendly composite board.
[0026] Embodiment 3: A method for preparing a deformation-resistant environmentally friendly composite board, specifically comprising: Step 1: Preparation of carboxylated bamboo fiber The bamboo fiber was washed with deionized water to remove dust and impurities, and then dried at 60°C to obtain dry bamboo fiber. 1.57 parts of 2,2,6,6-tetramethylpiperidine oxide, 10.2 parts of sodium bromide, 44.4 parts of sodium hypochlorite and 43.9 parts of deionized water were mixed and stirred to obtain tetramethylpiperidine oxide solution. 5 parts of dry bamboo fiber and 100 parts of tetramethylpiperidine oxide solution were mixed, and the pH was adjusted to 10.0 with sodium hydroxide solution. The reaction was carried out at 60°C and 300rpm for 1.0h. After the reaction was completed, the bamboo fiber was filtered out, washed with deionized water, and dried at 27°C for 24h to obtain carboxylated bamboo fiber.
[0027] Step 2: Preparation of Aminated Silsesquioxane By mass, 0.3 parts of tetramethylammonium hydroxide, 0.3 parts of triethylamine, 20 parts of ethanol, 10 parts of acetonitrile and 30 parts of deionized water were mixed to obtain a mixed amine solution. 20 parts of KH-550 were slowly added dropwise to 60.6 parts of the mixed amine solution, and refluxed at 70°C and 300rpm for 18h. After reflux, vacuum heating was performed to remove the solvent and the solution was washed with toluene to obtain amino silsesquioxane.
[0028] Step 3: Preparation of aminosiloxane-modified bamboo fiber By mass, 0.4 parts of amino silsesquioxane and 95.6 parts of deionized water were mixed and ultrasonically dispersed for 4 hours to obtain an amino silsesquioxane dispersion. 96 parts of the amino silsesquioxane dispersion and 4 parts of carboxylated bamboo fiber were mixed and reacted at 40°C for 12 hours. After the reaction was completed, it was filtered and dried at 60°C to obtain amino siloxane-modified bamboo fiber.
[0029] Step 4: Preparation of pyroglutamic acid-polyethylene glycol ester By mass, 12.5 parts of pyroglutamic acid, 48.3 parts of polyethylene glycol, and 0.04 parts of scandium trifluoromethanesulfonate were mixed, reacted at 180°C for 3 hours in nitrogen as a protective gas, heated to 200°C, and continued to react for 2 hours. After the reaction was completed, the temperature was lowered to 130°C, vacuum filtered, and dried to obtain pyroglutamic acid-polyethylene glycol ester.
[0030] Step 5: Prepare deformation-resistant environmentally friendly composite board By mass, 22 parts of aminosilicone modified bamboo fiber, 26 parts of pyroglutamic acid-polyethylene glycol ester and 57 parts of polylactic acid were mixed evenly, kneaded at 190°C for 30 minutes, cooled after kneading, and crushed to obtain composite board particles. The composite board particles were hot-pressed and compounded at a hot pressing pressure of 5MPa, a hot pressing temperature of 180°C, and a hot pressing time of 60min. After the hot pressing, they were cooled to 120°C and pressed again for shaping. The secondary shaping pressure was 5MPa and the secondary shaping time was 15min. After shaping, they were naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant environmentally friendly composite board.
[0031] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below: Comparative Example 1: No aminosilsesquioxane was added, and the other conditions were the same as those in Example 1.
[0032] A method for preparing an anti-deformation environmentally friendly composite board, specifically comprising: Step 1: Preparation of carboxylated bamboo fiber The bamboo fiber was washed with deionized water to remove dust and impurities, and then dried at 60°C to obtain dry bamboo fiber. 1.57 parts of 2,2,6,6-tetramethylpiperidine oxide, 10.2 parts of sodium bromide, 44.4 parts of sodium hypochlorite and 43.9 parts of deionized water were mixed and stirred to obtain tetramethylpiperidine oxide solution. 5 parts of dry bamboo fiber and 100 parts of tetramethylpiperidine oxide solution were mixed, and the pH was adjusted to 10.0 with sodium hydroxide solution. The reaction was carried out at 60°C and 300rpm for 1.0h. After the reaction was completed, the bamboo fiber was filtered out, washed with deionized water, and dried at 27°C for 24h to obtain carboxylated bamboo fiber.
[0033] Step 2: Preparation of pyroglutamic acid-polyethylene glycol ester By mass, 12.5 parts of pyroglutamic acid, 48.3 parts of polyethylene glycol, and 0.04 parts of scandium trifluoromethanesulfonate were mixed, reacted at 180°C for 3 hours in nitrogen as a protective gas, heated to 200°C, and continued to react for 2 hours. After the reaction was completed, the temperature was lowered to 130°C, vacuum filtered, and dried to obtain pyroglutamic acid-polyethylene glycol ester.
[0034] Step 3: Prepare anti-deformation environmentally friendly composite board By mass, 20 parts of carboxylated bamboo fiber, 25 parts of pyroglutamic acid-polyethylene glycol ester and 55 parts of polylactic acid were mixed evenly, kneaded at 190°C for 30 minutes, cooled after kneading, and crushed to obtain composite board particles. The composite board particles were hot-pressed and compounded at a hot pressing pressure of 5MPa, a hot pressing temperature of 180°C, and a hot pressing time of 60min. After the hot pressing, they were cooled to 120°C and pressed again for shaping. The secondary shaping pressure was 5MPa and the secondary shaping time was 15min. After shaping, they were naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant and environmentally friendly composite board.
[0035] Comparative Example 2: The silsesquioxane was not modified by amino reaction, and the other conditions were the same as those in Example 1.
[0036] A method for preparing an anti-deformation environmentally friendly composite board, specifically comprising: Step 1: Preparation of carboxylated bamboo fiber The bamboo fiber was washed with deionized water to remove dust and impurities, and then dried at 60°C to obtain dry bamboo fiber. 1.57 parts of 2,2,6,6-tetramethylpiperidine oxide, 10.2 parts of sodium bromide, 44.4 parts of sodium hypochlorite and 43.9 parts of deionized water were mixed and stirred to obtain tetramethylpiperidine oxide solution. 5 parts of dry bamboo fiber and 100 parts of tetramethylpiperidine oxide solution were mixed, and the pH was adjusted to 10.0 with sodium hydroxide solution. The reaction was carried out at 60°C and 300rpm for 1.0h. After the reaction was completed, the bamboo fiber was filtered out, washed with deionized water, and dried at 27°C for 24h to obtain carboxylated bamboo fiber.
[0037] Step 2: Preparation of silsesquioxane By mass, 20 parts of KH-550, 20 parts of ethanol, 10 parts of acetonitrile and 30 parts of deionized water were mixed, hydrochloric acid was added dropwise to adjust the pH, and the mixture was refluxed at 70°C and 300 rpm for 18 hours. After the reflux was completed, the mixture was heated in vacuum, the solvent was removed, and the mixture was washed with toluene to obtain silsesquioxane.
[0038] Step 3: Preparation of modified bamboo fiber By mass, 0.4 parts of silsesquioxane and 95.6 parts of deionized water were mixed and ultrasonically dispersed for 4 hours to obtain a silsesquioxane dispersion. 96 parts of the silsesquioxane dispersion and 4 parts of carboxylated bamboo fiber were mixed and reacted at 40°C for 12 hours. After the reaction was completed, it was filtered and dried at 60°C to obtain silsesquioxane-modified bamboo fiber.
[0039] Step 4: Preparation of pyroglutamic acid-polyethylene glycol ester By mass, 12.5 parts of pyroglutamic acid, 48.3 parts of polyethylene glycol, and 0.04 parts of scandium trifluoromethanesulfonate were mixed, reacted at 180°C for 3 hours in nitrogen as a protective gas, heated to 200°C, and continued to react for 2 hours. After the reaction was completed, the temperature was lowered to 130°C, vacuum filtered, and dried to obtain pyroglutamic acid-polyethylene glycol ester.
[0040] Step 5: Prepare deformation-resistant environmentally friendly composite board By mass, 20 parts of modified bamboo fiber, 25 parts of pyroglutamic acid-polyethylene glycol ester and 55 parts of polylactic acid were mixed evenly, kneaded at 190°C for 30 minutes, cooled after kneading, and crushed to obtain composite board particles. The composite board particles were hot-pressed and compounded at a hot pressing pressure of 5MPa, a hot pressing temperature of 180°C, and a hot pressing time of 60min. After the hot pressing, they were cooled to 120°C and pressed again for shaping. The secondary shaping pressure was 5MPa and the secondary shaping time was 15min. After shaping, they were naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant environmentally friendly composite board.
[0041] Comparative Example 3: No pyroglutamic acid was added, and the remaining conditions were the same as those in Example 1.
[0042] A method for preparing an anti-deformation environmentally friendly composite board, specifically comprising: Step 1: Preparation of carboxylated bamboo fiber The bamboo fiber was washed with deionized water to remove dust and impurities, and then dried at 60°C to obtain dry bamboo fiber. 1.57 parts of 2,2,6,6-tetramethylpiperidine oxide, 10.2 parts of sodium bromide, 44.4 parts of sodium hypochlorite and 43.9 parts of deionized water were mixed and stirred to obtain tetramethylpiperidine oxide solution. 5 parts of dry bamboo fiber and 100 parts of tetramethylpiperidine oxide solution were mixed, and the pH was adjusted to 10.0 with sodium hydroxide solution. The reaction was carried out at 60°C and 300rpm for 1.0h. After the reaction was completed, the bamboo fiber was filtered out, washed with deionized water, and dried at 27°C for 24h to obtain carboxylated bamboo fiber.
[0043] Step 2: Preparation of Aminated Silsesquioxane By mass, 0.3 parts of tetramethylammonium hydroxide, 0.3 parts of triethylamine, 20 parts of ethanol, 10 parts of acetonitrile and 30 parts of deionized water were mixed to obtain a mixed amine solution. 20 parts of KH-550 were slowly added dropwise to 60.6 parts of the mixed amine solution, and refluxed at 70°C and 300rpm for 18h. After reflux, vacuum heating was performed to remove the solvent and the solution was washed with toluene to obtain amino silsesquioxane.
[0044] Step 3: Preparation of aminosiloxane-modified bamboo fiber By mass, 0.4 parts of amino silsesquioxane and 95.6 parts of deionized water were mixed and ultrasonically dispersed for 4 hours to obtain an amino silsesquioxane dispersion. 96 parts of the amino silsesquioxane dispersion and 4 parts of carboxylated bamboo fiber were mixed and reacted at 40°C for 12 hours. After the reaction was completed, it was filtered and dried at 60°C to obtain amino siloxane-modified bamboo fiber.
[0045] Step 4: Prepare deformation-resistant environmentally friendly composite board By mass, 20 parts of aminosilicone modified bamboo fiber, 25 parts of polyethylene glycol and 55 parts of polylactic acid were mixed evenly, kneaded at 190°C for 30 minutes, cooled after kneading, and crushed to obtain composite board particles. The composite board particles were hot-pressed and compounded at a hot-pressing pressure of 5MPa, a hot-pressing temperature of 180°C, and a hot-pressing time of 60min. After the hot-pressing was completed, it was cooled to 120°C and pressed again for shaping. The secondary shaping pressure was 5MPa and the secondary shaping time was 15min. After shaping, it was naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant environmentally friendly composite board.
[0046] Detection experiment: The anti-deformation environmentally friendly composite boards required for the test were prepared according to the preparation methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.
[0047] Bending strength test: According to "Wood Plastic Decorative Panel" (GB / T 24137-2009), a universal mechanical testing machine was used to test. Samples were cut from the 6 prepared high-strength wear-resistant coated panels. The sample size was 170mm×50mm×6mm. The sample was placed flat on the support, and the load was applied to the center of the sample at a uniform speed. The maximum load applied when the sample was destroyed was recorded, and the bending strength of each sample was calculated.
[0048] Impact resistance test: The test was conducted in accordance with the Test Methods for Physical and Chemical Properties of Wood-Based Panels and Faced Wood-Based Panels (GB / T 17657-2013). Samples were cut from the six prepared high-strength wear-resistant coated panels. The sample size was 300mm×180mm×6mm. The sample was fixed on a fixture and a piece of carbon paper was placed on the sample. A steel ball with a diameter of 42.8mm and a mass of 324g was used to freely and vertically impact the middle of the sample from 1.75m above the sample to measure the indentation diameter.
[0049] Dimensional stability test: According to the "Test Methods for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards" (GB / T 17657-2013), two batches of samples were cut from the prepared 6 kinds of high-strength wear-resistant coated boards. The sample size was 120mm×120mm×6mm. They were cured in a constant temperature and humidity environment at 23℃ and a relative humidity of 50% for 72 hours. The midpoints of each side were marked and the distances between the midpoints of the horizontal and longitudinal sides were measured (through the center of the sample). One batch of samples was air-dried at 70℃, cooled to room temperature after drying for 24 hours, cooled for 1 hour, and the relative distances between the midpoints were measured. Another batch of samples was placed in a constant temperature and humidity environment at 40℃ and a relative humidity of 90% for 96 hours. After the treatment, the relative distances between the midpoints were also measured to calculate the dimensional stability of the samples.
[0050]
[0051] Conclusion: It can be seen from the experiment that the deformation-resistant environmentally friendly composite board prepared by the preparation method of Example 1 is superior to the deformation-resistant environmentally friendly composite board prepared by the preparation methods of Comparative Example 1, Comparative Example 2 and Comparative Example 3 in the bending strength test, impact resistance test and dimensional stability test, which effectively solves the problem that the stability and impact resistance of the wood-plastic composite board are not good enough.
[0052] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing an anti-deformation environmentally friendly composite board, characterized in that: The preparation method is: The aminosilicone modified bamboo fiber, pyroglutamic acid-polyethylene glycol ester and polylactic acid are mixed evenly, kneaded at 180-200°C for 25-35 minutes, cooled after kneading, and crushed to obtain composite board particles, and the composite board particles are hot-pressed at a pressure of 4-6 MPa, a temperature of 170-190°C, and a time of 50-70 minutes. After the hot pressing is completed, the composite board particles are cooled to 110-130°C, pressed again for shaping, the secondary shaping pressure is 4-6 MPa, and the secondary shaping time is 10-20 minutes. After shaping, the composite board is naturally cooled to room temperature, taken out, and trimmed to obtain a deformation-resistant environmentally friendly composite board.
2. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 1, characterized in that: The mass ratio of modified bamboo fiber, pyroglutamic acid-polyethylene glycol ester and polylactic acid is (18-22):(24-26):(53-57).
3. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 1, characterized in that: The preparation method of aminosiloxane modified bamboo fiber is as follows: The bamboo fiber is washed with deionized water to remove dust and impurities, and then dried at 55-65° C. to obtain dried bamboo fiber; 2,2,6,6-tetramethylpiperidinium oxide, sodium bromide, sodium hypochlorite and deionized water are mixed and stirred evenly to obtain tetramethylpiperidinium oxide solution; the dried bamboo fiber and the tetramethylpiperidinium oxide solution are mixed, the pH is adjusted to be alkaline, and the mixture is reacted at 55-65° C. and 200-400 rpm for 0.5-1.5 h; after the reaction is completed, the bamboo fiber is filtered out, washed with deionized water, and dried at 25-30° C. for 22-26 h to obtain carboxylated bamboo fiber; Tetramethylammonium hydroxide, triethylamine, ethanol, acetonitrile and deionized water are mixed to obtain a mixed amine solution, KH-550 is slowly added dropwise to the mixed amine solution, refluxed at 65-75°C and 200-400rpm for 16-20h, and after refluxed, vacuum heated, the solvent is removed, and washed with toluene to obtain amino silsesquioxane; The aminosilsesquioxane and deionized water are mixed, and ultrasonically dispersed for 3 to 5 hours to obtain an aminosilsesquioxane dispersion. The aminosilsesquioxane dispersion and carboxylated bamboo fiber are mixed, and reacted at 35 to 45° C. for 10 to 14 hours. After the reaction is completed, the mixture is filtered and dried at 55 to 65° C. to obtain aminosiloxane-modified bamboo fiber.
4. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 3, characterized in that: The tetramethylpiperidinium oxide solution includes 1.56 to 1.58 parts of 2,2,6,6-tetramethylpiperidinium oxide, 10.0 to 10.4 parts of sodium bromide, 44.2 to 44.6 parts of sodium hypochlorite, and 43.5 to 44.5 parts of deionized water in parts by mass.
5. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 3, characterized in that: The mixed amine solution includes, by mass, 0.2 to 0.4 parts of tetramethylammonium hydroxide, 0.2 to 0.4 parts of triethylamine, 18 to 22 parts of ethanol, 8 to 12 parts of acetonitrile, and 28 to 32 parts of deionized water.
6. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 3, characterized in that: The aminosiloxane-modified bamboo fiber comprises 0.3-0.5 parts of aminosilsesquioxane, 3-5 parts of carboxylated bamboo fiber and 90-100 parts of deionized water in parts by mass.
7. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 1, characterized in that: The preparation method of pyroglutamic acid-polyethylene glycol ester is: Mix pyroglutamic acid, polyethylene glycol and scandium trifluoromethanesulfonate, react at 170-190°C for 2-4h in nitrogen as protective gas, heat to 195-205°C, continue to react for 1-3h, cool to 125-135°C after the reaction is completed, vacuum filter and dry to obtain pyroglutamic acid-polyethylene glycol ester.
8. The method for preparing a deformation-resistant environmentally friendly composite board according to claim 7, characterized in that: In parts by mass, the pyroglutamic acid-polyethylene glycol ester includes 12.3 to 12.7 parts of pyroglutamic acid, 48.1 to 48.5 parts of polyethylene glycol, and 0.03 to 0.05 parts of scandium trifluoromethanesulfonate.
Citation Information
Patent Citations
Therapeutic modifiers of the reverse mode of ATP synthase
CA3050553A1
Method for preparing regenerated cellulose spherical aerogel modified through carboxylation
CN103570967A
Method for modifying waterborne wood coating by hybridizing one-dimensional nano-cellulose by virtue of two-dimensional graphene oxide
CN105754470A
Process for making pulp
US20140305603A1
